TEA PACKAGING DESIGN USING INTEGRATION OF KANSEI ENGINEERING AND EYE TRACKING FOR ENHANCING CONSUMER APPEAL - Cahyawati, Amanda Nur; Fathimahhayati, Lina Dianati; Tontowi, Alva Edy (JEMIS (Journal of Engineering & Management in Industrial System), 2024)
This research aims to determine the design specifications for tea drink packaging that appeal to consumers using Kansei and eye-tracking techniques. Kansei Engineering focuses on developing products that align with consumers' feelings and emotional needs. Eye-tracking provides insights into how consumers see and interact with packaging, as evidenced by total fixation duration, allowing for the identification of design elements that attract the most attention and influence consumer perception. The application of eye-tracking and Kansei Engineering helps match customer perceptions of products with their functional and technical specifications, providing a holistic and effective approach to increasing sales and consumer satisfaction. Integrating these two methods makes the design process more consumer-focused, combining emotional and visual appeal, thereby increasing attractiveness and potential consumption. The urgency of this research lies in its potential to revitalize the tea industry in Indonesia by utilizing innovative packaging designs. Enhancing consumer appeal to tea products through the integration of Kansei Engineering and eye-tracking, which are visually and emotionally engaging, addresses the main obstacle to low tea consumption in Indonesia. Thus, it contributes to the growth of the tea market and promotes healthier beverage choices among Indonesian consumers. The research results show that an aesthetic packaging design requires a sports cap type lid, a convex bottle body, a plain motif, and a square cross-section. Ergonomic packaging design requires a flip cap type lid, a wave-shaped bottle body, a textured motif, and a round cross-section. Simple packaging design requires a straw cap type lid, a serrated bottle body, a plain motif, and a square cross-section. This research aims to revitalize Indonesia's tea industry through consumer-oriented packaging design, increasing emotional and visual appeal. Key implications include increased consumer appeal, potential for increased consumption, better marketing strategies, and packaging design innovation that resonates emotionally with consumers.